2014
DOI: 10.1038/srep03931
|View full text |Cite
|
Sign up to set email alerts
|

A30P α-Synuclein interferes with the stable integration of adult-born neurons into the olfactory network

Abstract: Impaired olfaction is an early symptom in Parkinson disease (PD), although the exact cause is as yet unknown. Here, we investigated the link between PD-related mutant α-Synuclein (α-SYN) pathology and olfactory deficit, by examining the integration of adult-born neurons in the olfactory bulb (OB) of A30P α-SYN overexpressing mice. To this end, we chose to label one well-known vulnerable subpopulation of adult-born cells, the dopaminergic neurons. Using in vivo two-photon imaging, we followed the dynamic proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 61 publications
2
16
1
Order By: Relevance
“…OB neurogenesis was also examined in the latter experiment but no difference in the number of newly generated neurons in the OB, based on BrdU labeling assays, was detected. Instead, it is likely that the olfaction deficits observed in SNCA transgenic mice are due, at least in part, to impaired growth and branching of dendrites and the subsequent failed stable integration into the OB of newly born DA neurons during adult neurogenesis, leading to a decrease in cell survival, as has been described for an A30P SNCA overexpressing mouse [182,183].…”
Section: Snca (Park1/park4)mentioning
confidence: 97%
“…OB neurogenesis was also examined in the latter experiment but no difference in the number of newly generated neurons in the OB, based on BrdU labeling assays, was detected. Instead, it is likely that the olfaction deficits observed in SNCA transgenic mice are due, at least in part, to impaired growth and branching of dendrites and the subsequent failed stable integration into the OB of newly born DA neurons during adult neurogenesis, leading to a decrease in cell survival, as has been described for an A30P SNCA overexpressing mouse [182,183].…”
Section: Snca (Park1/park4)mentioning
confidence: 97%
“…Regarding the translation of preclinical data to clinical practise, impairment of olfaction may precede Parkinson’s disease in otherwise asymptomatic olfactory function [ 122 , 123 ]. An experimental model of Parkinson’s disease revealed a decrease of the odor discrimination and concominant reduction of neurogenesis [ 124 ]. The purpose of the upcoming preclinical study is enhancement of neurogenesis in the senescent or neurodegenerative brain and recovery of brain functions [ 125 , 126 ].…”
Section: Radiation-induced Changesmentioning
confidence: 99%
“…Previous studies in our lab and others have indicated that olfactory dysfunction, which is a non-motor symptom of PD that can precede onset of motor symptoms by many years, is inherent in experimental models of PD and Mn neurotoxicity (Dranka et al, 2014; Neuner et al, 2014; Ngwa et al, 2014; Zhang et al, 2015). We therefore performed a social discrimination test to examine the effects of Mn exposure on olfaction.…”
Section: Resultsmentioning
confidence: 94%
“…Anxiolytic and depressive phenotyping were outside the scope of this paper, but would provide valuable insight and should be explored in future studies. In terms of non-motor deficits, olfactory deficits found in Mn-treated mice during this study (Figure 1H) could potentially be due to increased protein aggregation, reductions in neurogenesis, or changes in the olfactory epithelium or receptors (Chiu et al, 2015; Kurtenbach et al, 2013; Neuner et al, 2014; Postuma and Berg, 2016).…”
Section: Discussionmentioning
confidence: 95%